Changing the Adverse Event Profile in Metastatic Spine Surgery: An Evidence-Based Approach to Target Wound Complications and Instrumentation Failure. (15th October 2016) - Mesfin, Addisu; Sciubba, Daniel M.; Dea, Nicolas; Nater, Anick; Bird, Justin E.; Quraishi, Nasir A.; Fisher, Charles G.; Shin, John H.; Fehlings, Michael G.; Kumar, Naresh; Clarke, Michelle J.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Systematic review. Objective: To identify risk factors and preventive methods for wound complications and instrumentation failure after metastatic spine surgery. Summary of Background Data: We focused on two postoperative complications of metastatic spine tumor surgery: wound complications and instrumentation failure and preventive measures. Methods: We performed a systematic review of the literature from 1980 to 2015. The articles were analyzed for the presence of documented infection and/or wound complications and instrumentation failure. Results: Forty articles met our inclusion criteria for wound complications and prevention. There is very low level of evidence that preoperative radiation, preoperative neurological deficit, revision procedures, and posterior approaches can contribute to wound complications (infections, wound dehiscence). There is very low level of evidence that plastic surgery soft tissue reconstruction, intrawound vancomycin powder, and percutaneous pedicle screws may prevent postoperative wound complications. Fourteen articles met our inclusion criteria for instrumentation failure. There is very low level of evidence that constructs greater than six levels, positive sagittal balance, preoperative radiation, and history of chest wall resection can contribute to implant failures. Conclusion: For patients undergoing revision metastatic spine tumor surgery, plastic surgery should perform the soft tissue reconstruction (strong recommendation/very low quality of evidence). For patients undergoing metastatic spine tumor surgery, plastic surgery may perform immediate soft tissue reconstruction (weak recommendation/very low quality of evidence). For patients undergoing metastatic spine tumor surgery, intrawound vancomycin can be applied to decrease the risk of postoperative wound infections (weak recommendation/very low quality of evidence). For patients undergoing metastatic spine tumor surgery, percutaneous pedicle screws can be placed to decrease the risk of postoperative wound complications (weak recommendation/very low quality of evidence). Instrumentation failure risk factors include constructs greater than six levels, positive sagittal balance, preoperative radiation, and history of chest wall resections (weak recommendation/very low quality of evidence). Level of Evidence: N/A